Bioaktivitas dan Kandungan Senyawa Kimia Tumbuhan Merung (Coptosapelta tomentosa): Bioactivity and Chemical Compounds of Merung Plants (Coptosapelta tomentosa) - Erwin Erwin; Usman Usman (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Coptosapelta tomentosa (synonym: Coptosapelta flavescens Korth) is a medicinal plant that is widely used traditionally. Coptosapelta tomentosa is known locally as Merung in East Kalimantan. In traditional medicine, Merung root is used to treat diarrhea, recovery from childbirth, anti-malarial, relieve colic, ulcers, colds, fever and vaginal discharge. Based on the results of the literature study, it shows that the compounds contained in Merung have the potential as anticancer, anti-inflammatory, antibacterial, and antioxidant. Keywords: Coptosapelta tomentosa, Merung, anticancer, and traditional Abstrak Coptosapelta tomentosa (sinonim: Coptosapelta flavescens Korth) merupakan salah satu tumbuhan obat yang banyak digunakan secara tradisional. Coptosapelta tomentosa dikenal dengan nama lokal Merung di Kalimantan Timur. Dalam pengobatan tradisional, akar Merung digunakan untuk mengobati diare, pemulihan persalinan, anti-malaria, meredakan kolik, bisul, masuk angin, demam dan keputihan. Berdasarkan hasil kajian litetaratur menunjukkan senyawa-senyawa yang terkandung dalam Merung berpotensi sebagai antikanker, antiinflamasi, antbakteri, dan antioksidan. Kata Kunci: Coptosapelta tomentosa, Merung, antikanker, dan tradisional